Relationship of Students Motivation with National Competency Exam Result in the Nurse Profession Program of Immanuel School of Health Sciences Bandung - Natalia, Lidya; Sinaga, Anni (KnE Life Sciences, 2021)
Nurses must have a Certificate of Registration and a Certificate of Competency in order to carry out nursing practices in Indonesia. One of the ways to measure nurse competency standards and obtain the Certificate of Competency is through the National Competency Exam. Identifying obstacles is one method used to evaluate the high number of alumni failures in the National Competency Exam. One obstacle that affects students is motivation. The purpose of this study was to analyze the relationship between students motivation and their success when taking the National Competency Exam. The student subjects were alumni from batch 28 of the Nurse Profesion Program of Immanuel School of Health Sciences Bandung. 72 people were selected using the accidental sampling method. The instrument in this study was a student motivation questionnaire and the results of the National Competency Exam in October 2018 which had been tested for validity and reliability. Bivariate analysis was performed using the Chi Square statistical test with p ≤ 0.05. The results showed p-value of 0.561> 0.05, this suggests that there is no significant relationship between student motivation and the exam results. It is therefore suggested that nursing educators explore other factors which could produce poor scores when taking the National Competency Exam. Keywords: Students’ Motivation, National Competency Exam, Nurse Profession Program